The Authority of Judicial Orders of the Constitutional Court A Study of Legal Construction and Separation of Powers in Indonesia - Ramdhani, Syafiq; Negara, Tunggul Anshari Setia; Susmayanti, Riana (Faculty of Law, Merdeka University Surabaya, Indonesia, 2025)
This study discusses the authority of judicial orders issued by the Constitutional Court in the context of legal construction and the principle of separation of powers in Indonesia. Judicial orders, as a concrete form of the expansion of the role of the judiciary, play an important role in filling legal gaps and ensuring the implementation of the Constitution, especially when the executive and legislative branches fail to fulfill their obligations. This study employs a normative legal approach with three analytical methods: a statutory approach, a case study of Constitutional Court decisions, and a conceptual approach to relevant legal theories. The findings indicate that judicial orders in Indonesia are not supported by a strong implementation framework, unlike practices in other countries such as India, Colombia, South Africa, Austria, and Germany, which are more progressive in regulating and supervising the implementation of judicial orders. The Indonesian Constitutional Court tends to issue declaratory or conditional rulings, but effective follow-up mechanisms do not accompany these. Therefore, this study recommends reformulating rulings to be more operational, establishing an implementation oversight unit, and adopting a continuing mandamus model for strategic issues as part of efforts to strengthen the role of the Constitutional Court in upholding constitutional supremacy and substantive justice in a constitutional democracy.